One-step and scalable synthesis of Ni2P nanocrystals encapsulated in N, P-codoped hierarchically porous carbon matrix using a bipyridine and phosphonate linked nickel metal–organic framework as highly efficient electrocatalysts for overall water splitting. (20th February 2019) - Yan, Liting; Jiang, Huimin; Wang, Ying; Li, Liangjun; Gu, Xin; Dai, Pengcheng; Liu, Dandan; Tang, Si-Fu; Zhao, Guoming; Zhao, Xuebo; Thomas, K. Mark
Abstract: The development of highly active and durable noble-metal-free electrocatalysts for overall water splitting is a great challenge. Herein, a microdroplet flow reaction is used for ultrafast and continuous synthesis of a nickel metal–organic framework material with 4, 4ʹ-bipyridine and phosphonate ligands. A one step pyrolysis of this metal–organic framework to various heat treatment temperatures and hold times at maximum temperature give a range of electrocatalysts, containing crystalline Ni2 P nanoparticles dispersed in a porous carbonaceous matrix incorporating relatively high concentrations of both nitrogen and phosphorus derived from the original metal–organic framework. The Ni2 P electrocatalysts inherite the morphology of the metal–organic framework precursor, have a uniform dispersion of Ni2 P sites and Brunauer-Emmett-Teller surface areas in the range 558–754 m 2  g −1 . The Ni2 P electrocatalysts exhibit excellent catalytic performance for both hydrogen and oxygen evolution reactions in 1.0 M KOH and an electrolyzer using Ni2 P electrocatalysts as both cathode and anode generates a current density of 10 mA cm −2  at a voltage of 1.62 V with superior durability. This facile and scalable synthesis strategy for the rational design of electrocatalysts represents a proof-of-concept with the potential for scale-up for use in practical applications. Highlights: Ni2 P-NPCM were synthesized using one-step pyrolysis of metal–organic frameworks without additional phosphorus sources. The facile MOF synthesis combined with pyrolysis to synthesize the electrocatalyst was easily achieved on the gram-scale. Ni2 P-NPCM can serve as a highly efficient electrocatalyst for overall water splitting in an alkaline electrolyte.